A Phase I Study of Dasatinib with Concurrent Chemoradiation for Stage III Non-Small Cell Lung Cancer - Safran, Howard; DiPetrillo, Thomas; Khurshid, Humera; Ng, Thomas; Mantripragada, Kalyan; Birnbaum, Ariel; Berz, David; Radie-Keane, Kathy; Perez, Kimberly; Constantinou, Maria; Luppe, Denise; Schumacher, Andrew; et al. (Frontiers in Oncology, 2012)
Objectives: Src family kinases (SFKs) are expressed in non-small cell lung cancer (NSCLC) and may be involved in tumor growth and metastases. Inhibition of SFK may also enhance radiation. The purpose of this study was to evaluate if a maximum dose of 100 mg of dasatinib could be safely administered with concurrent chemoradiation and then continued as maintenance for patients with newly diagnosed stage III NSCLC. Methods: Patients with stage III locally advanced NSCLC received paclitaxel, 50 mg/m2/week, with carboplatin area under the curve (AUC) = 2, weekly for 7 weeks, and concurrent radiotherapy, 64.8 Gy. Three dose levels of dasatinib 50, 70, and 100 mg/day were planned. Results: 11 patients with locally advanced NSCLC were entered. At the 70 mg dose level 1 patient had grade 5 pneumonitis not responsive to therapy, and one patient had reversible grade 3 pneumonitis and grade 3 pericardial effusion. Due to these toxicities the Brown University Oncology Group Data Safety Monitoring Board terminated the study. Conclusion: Dasatinib could not be safely combined with concurrent chemoradiation for stage 3 lung cancer due to pneumonitis.